Effect of circuit dumbbell-weight training on the volleying and digging skills of volleyball players at the University of Benin - Leghemo, Tinimotei Stephen (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
The study was aimed at determining the effect of an 8-week circuit dumbbell-weight training on the digging and volleying skills of University of Benin volleyball players. Two (2) researchable questions were raised and two (2) hypotheses were also formulated in line with the questions. The “pre-test, post-test experimental control group research design” was employed for this study. The population of the study was made up of 72 volleyball players with a sample size of thirty-six (36) players comprising (18) male and (18) female volleyball players who were selected for the study using a simple random sampling technique. The sampling technique involved balloting by replacement. The study was a field test constructed by the researcher with expert approval involving volleyball digging, process, product, and protocol. The Fundamental Skill Data Capture Device (FSDCD) was used to record the test results. The experimental group took part in an 8-week training programme which was supervised by the researcher with the assistance of the school’s volleyball coach. After the intervention training programme, two tests (posttest) were conducted. One on the control group and another on the experimental group. Data were analyzed using a T-Test based on the findings of the study. The outcome of the study indicated that the intervention (experimental) group had a high mean value compared to their control group in both the digging process-product-protocol and volleying process-product-protocol tests of the volleyball game. It was recommended that the use of a well-structured circuit dumbbell-weight training programme should form part of every coach’s tool for training university volleyball players.